Malaria amidst COVID-19 in India: Challenges, Efforts, and Recommendations - Anmol Mohan; Um Ul Wara; Syeda Wania Amjad; Sudhan Rackimuthu; Reem Hunain; Hiba Khan; Ana Carla dos Santos Costa; Shoaib Ahmad; Mohammad Yasir Essar (Elsevier, 2021)
Since the outbreak of COVID-19 in India, the country has faced a slew of new challenges, spawning a slew of other deadly viruses and diseases while also serving as a breeding ground for them. Not only did Malaria (a vector-borne disease) emerge as a coincidental outbreak during the pandemic, but many others did as well, causing severe diseases in humans due to flaws in health-care systems that were already overburdened with identifying, preventing, and treating the recently introduced coronavirus disease. Inadequate water cleanliness, as well as the delayed and misdiagnosis of Malaria with COVID-19 due to overlapping symptoms, are major impediments in the incidence of these unique outbreaks. Appropriate steps, such as providing clean water and diagnostic facilities to control Malaria cases, should be adopted to prevent such epidemics in the country.